2018
DOI: 10.1088/1741-4326/aaa8d0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of liquid lithium film formation and deuterium retention on hot W samples studied by LID-QMS. Implications for future fusion reactors

Abstract: Liquid metal (LM) divertor concepts explore an alternative solution to the challenging power/particle exhaust issues in future magnetic fusion reactors. Among them, lithium (Li) is the most promising material. Its use has shown important advantages in terms of improved H-mode plasma confinement and heat handling capabilities. In such scenario, a possible combination of tungsten (W) on the first wall and liquid Li on the divertor could be an acceptable solution, but several issues related to material compatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
6
2
Order By: Relevance
“…While, using Li films, Capece et al observed the formation of LiD films after Li exposure to D ion beam and D retention was found to decrease with the increasing temperature and a release peak at 390 • C was also spotted for the LiD film [35]. Recently, in [36] Castro et al have found that HI retention in lithium can be significantly reduced at the surface with high temperature. All together these results suggest that operation at higher temperatures (>∼500 • C) may prevent the strong trapping of HI in Li.…”
Section: Introductionmentioning
confidence: 99%
“…While, using Li films, Capece et al observed the formation of LiD films after Li exposure to D ion beam and D retention was found to decrease with the increasing temperature and a release peak at 390 • C was also spotted for the LiD film [35]. Recently, in [36] Castro et al have found that HI retention in lithium can be significantly reduced at the surface with high temperature. All together these results suggest that operation at higher temperatures (>∼500 • C) may prevent the strong trapping of HI in Li.…”
Section: Introductionmentioning
confidence: 99%
“…The deuterium recycling coefficient at the various surfaces in experiment is very uncertain, with strong dependencies on the temperature and relative particle fluxes of the deuterium and lithium species [9,27,28]. Generally, it is expected that deuterium absorption above 400 • C-500 • C falls off rapidly due to thermal decomposition of lithium deuteride, though below this temperature deuterium absorption is high.…”
Section: Sensitivity To Deuterium Recyclingmentioning
confidence: 99%
“…(b) The retention of evaporated or plasma injected lithium on W at several temperatures was investigated in order to assess its impact on a fusion reactor operating with hot first wall. It was concluded [53] that an exponentially decaying retention as the first-wall temperature is increased takes place, with negligible D/Li ratios at T > 350 • C. On the other hand, D retention of liquid Sn and LiSn alloys was studied in DC glow discharges of D. Retention of H isotopes in the form of bubbles has been observed in liquid tin exposed to high D fluxes. This has been attributed to the low solubility and diffusivity of D into Sn.…”
Section: Power Exhaust: Liquid Metalsmentioning
confidence: 99%